Two Cases of Breakthrough Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infections Caused by the Omicron Variant (B.1.1.529 Lineage) in International Travelers to Japan - Maruki, Taketomo; Iwamoto, Noriko; Kanda, Kohei; Okumura, Nobumasa; Yamada, Gen; Ishikane, Masahiro; Ujiie, Mugen; Saito, Masumichi; Fujimoto, Tsuguto; Kageyama, Tsutomu; Saito, Tomoya; Saito, Shinji; et al. (Clinical infectious diseases, 2022)
Abstract In November 2021, the World Health Organization designated a new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant of concern, Omicron (PANGO lineage B.1.1.529). We report on the first 2 cases of breakthrough coronavirus disease 2019 (COVID-19) caused by Omicron in Japan among international travelers returning from the country with undetected infection. The spread of infection by Omicron were considered.